Irregularity as a unifying principle of the novel trilogy by Stanislav Komarek - Antos, Matej (Bohemica Olomucensia, 2020)
The study focuses on the works of prose by contemporary Czech philosopher, biologist and essayist Stanislav Komarek, specifically on three novels, sometimes referred to as ``irregular trilogy'': Opslstisova nadace (Opslstis Foundation, 2002), Cerny domecek (Black House, 2004) and Mandarini (Mandarins, 2007). With the use of analytical-interpretive probes the study aims to find out and prove whether the principle of irregularity itself might work as a connecting link between the texts on different levels, especially regarding the genre structure, fictional setting and the way how aluctions and mystifications are utilized within the texts.
Keywords: Stanislav Komarek; irregular trilogy; contemporary Czech prose; literary analysis; postmodern literature